Suhu dan rasio kukus optimum pada proses gasifikasi kukus berkatalis K2CO3 terhadap arang batu bara lignit hasil pirolisis dengan laju pemanasan terkontrol - Dewi Tristantini; Ricky Kristanda Suwignjo (Jurnal Rekayasa Proses, 2014)
In order to fulfill the raw material needs of Fischer Tropsch process for producing synthethic fuel (synfuel), high yield of synthesis gas (syngas) with H2/CO ratio ≈ 2.0 should be obtained from lignite coal gasification. Steam gasification can enhance H2 composition in syngas. Lower activation energy of gasification reaction can be obtained using K2CO3 catalyst during the process. Pyrolysis step with controlled heating rate will affect pore surface area of char which will influence the composition and yield of syngas. In this study, lignite char from pyrolysis with controlled heating rate with 172.5 m2/g surface area and K2CO3 catalyst was fed in fixed bed steam gasification reactor. Steam to char mass ratio (2.0; 3.0; 4.0) and gasification temperature (675; 750; 825°C) was varied. Optimum condition for syngas production obtained in this study was steam gasification at 675°C with steam/char mass ratio 2.0. This condition will produce syngas with H2/CO ratio 2.07 and gas yield 1.128 mole/mole C (45% carbon conversion).